2022
DOI: 10.48550/arxiv.2201.11135
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HOLISMOKES. VIII. High-redshift, strong-lens search in the Hyper Suprime-Cam Subaru Strategic Program

Yiping Shu,
Raoul Cañameras,
Stefan Schuldt
et al.

Abstract: We carry out a dedicated search for strong-lens systems with high-redshift lens galaxies with the goal of extending strong lensingassisted galaxy evolutionary studies to earlier cosmic time. Two strong-lens classifiers are constructed from a deep residual network and trained with datasets of different lens redshift and brightness distributions. We classify a sample of 5,356,628 pre-selected objects from the Wide layer fields in the second public data release of the Hyper Suprime-Cam Subaru Strategic Program (H… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 75 publications
(118 reference statements)
0
2
0
Order By: Relevance
“…Since there are already thousands of known lens candidates in HSC (e.g., Wong et al 2018;Sonnenfeld et al 2019Sonnenfeld et al , 2020Jaelani et al 2020a,b;Jaelani et al in prep. ;Cañameras et al 2021a;Shu et al 2022), and we expect hundreds of thousands more observed by LSST and Euclid (Collett 2015), CNNs would be perfectly suited to analyze this amount of data in an acceptable amount of time.…”
Section: Neural Network and Their Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…Since there are already thousands of known lens candidates in HSC (e.g., Wong et al 2018;Sonnenfeld et al 2019Sonnenfeld et al , 2020Jaelani et al 2020a,b;Jaelani et al in prep. ;Cañameras et al 2021a;Shu et al 2022), and we expect hundreds of thousands more observed by LSST and Euclid (Collett 2015), CNNs would be perfectly suited to analyze this amount of data in an acceptable amount of time.…”
Section: Neural Network and Their Architecturementioning
confidence: 99%
“…Since we gained in our lens search projects (Cañameras et al 2021b;Cañameras et al in prep. ;Shu et al 2022) better performance by applying a square-root stretching, we also tested this for our modeling network. Hence, we did no longer pass the images to the network, but rather the square-root of the images after setting all negative background pixels to zero.…”
Section: Variations Of the Input Datamentioning
confidence: 99%